The Effect of Tricalcium Silicate (C3S) Percentage in Clinkerson the Cement Quality - ., Marhaini; Sri Yusmartini, Eka; Aini, Kurnia (International Journal of Engineering and Technology, 2021)
Composite cement products produced by national cement factories in Indonesia should follow the required quality standards. The quality standard of composite cement refers to the SNI 7064:2014. Some physical parameters of the quality standards set are mortar compressive strength and autoclave expansion. Compressive strength is influenced by C3S and C2S in the clinker. The reaction of the formation of mineralogical compounds occurs when clinkers formed. Whereas the expansion by autoclave is influenced by the levels of free lime in the cement. This research was conducted to determine the effect of the percentage of tricalcium silicate (C3S) on the quality of cement with free lime <2% and free lime > 2% with variations of C3S in clinkers, namely 55%, 57%, 59%, 61%, 63%, 65%, and 67%. Physical parameters tested in this study are compressive strength of mortar, blaine, and autoclave expansion. While the chemical parameters tested in this study are free lime in cement and SO3. Based on the research, it was found that if the same percentage of C3S quality of cement having FCaO <2%, the initial compressive strength results were greater than FCaO> 2%, the ideal condition of the development of compressive strength for FcaO > 2%, 3 to 7 days was at the percentage of C3S clinker of 63,48%. Whereas the development of ideal compressive strength for 7 to 28 days is at the clinker C3S percentage of 64,85%. For FCaO <2% the ideal condition 3 days to 7 days is at the percentage of clinker C3S of 62,79% and the development of compressive strength 7 to 28 days is at the percentage of clinker C3S of 54.77%. The expansion with autoclave experiencing expansion that does not meet the minimum requirements of SNI 7064:2014 are samples with a percentage of C3S 54,86% and 61% with FCaO > 2%.Â